Effectiveness of high-intensity interval training on cardiovascular rehabilitation: A systematic review - Fernández-Ortega, Javier; Fernández-Revelles, Andrés B. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This systematic review evaluated the effectiveness of high-intensity interval training (HIIT) in cardiovascular rehabilitation, analyzing its impact on cardiorespiratory capacity and quality of life in patients with heart disease. Searches were conducted in PubMed and Web of Science up to 01/08/2024 using MeSH terms related to “heart disease” and “physical exercise” (“High-Intensity Interval Training” AND “Heart Diseases” OR “Heart Failure”). The results showed that HIIT significantly improves VO2max and cardiac function, outperforming moderate-intensity continuous training (MICT). Additionally, it enhances patients’ autonomy and well-being without increasing adverse event risk. In conclusion, HIIT is established as a key strategy in cardiac rehabilitation, providing significant improvements in cardiorespiratory fitness and quality of life for patients with heart disease. Its implementation optimizes resources in rehabilitation programs, offering an efficient alternative to MICT. However, it is crucial to continue conducting long-term studies to validate its efficacy and safety across different populations and clinical settings.